2019
DOI: 10.1159/000496458
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of Serum β-Carotene and β-Carotene/Retinol Ratio Are Associated with Histological Severity in Nonalcoholic Fatty Liver Disease Patients

Abstract: β-Carotene has been reported to alleviate hepatic steatosis (SS), inflammation, and fibrosis in vivo and vitro studies. However, the clinical relevance of serum β-carotene and β-carotene-to-retinol (SC/SR) ratio with histological severity in nonalcoholic fatty liver disease (NAFLD) patients is unknown. This case-control study enrolled 24 control subjects and 62 NAFLD patients. Liver biopsies were collected and histological characteristics were assessed. Information with regard to demographic, anthropometric an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
(26 reference statements)
1
9
0
Order By: Relevance
“…According to this, the researchers indicated that both β-carotene and SC/SR decreased gradually with the progression of the disease—from the normal liver, hepatic steatosis, to the limit of steatohepatitis. These results showed that a lower concentration of circulating β-carotene and an SC/SR ratio are associated with the histological severity of NAFLD [130].…”
Section: Carotenoids and Hepatic Healthmentioning
confidence: 99%
“…According to this, the researchers indicated that both β-carotene and SC/SR decreased gradually with the progression of the disease—from the normal liver, hepatic steatosis, to the limit of steatohepatitis. These results showed that a lower concentration of circulating β-carotene and an SC/SR ratio are associated with the histological severity of NAFLD [130].…”
Section: Carotenoids and Hepatic Healthmentioning
confidence: 99%
“…The incorporation of carotenoids in therapeutic diets against steatosis is of great interest since serum β-carotene levels in patients with NAFLD (with clinical signs of liver steatosis, inflammation and fibrosis) are significantly lower than in healthy subjects. Therefore, various authors have described that a higher consumption of this carotenoid in the diet from food sources is associated with a lower risk of primary liver cancer [ 7 , 8 ]. Vegetables such as spinach and tomato are a good source of dietary carotenoids, with values that can reach 10.87 and 7.82 mg/100 g of fresh weight, respectively [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Handcrafted BPO has total carotenoid content ranging from 1661 to 1,890 mg/kg (Albuquerque et al., 2005; Aquino et al., 2012; Garcia‐Quiroz et al., 2003; Silva et al., 2009). In humans, low levels of serum β‐carotene (Christensen & Thomas Lawler, 2019; Wang et al., 2019; Xiao et al., 2019) and lower intake (Christensen & Thomas Lawler, 2019) are positively correlated with the severity of the hepatic injury caused by NAFLD.…”
Section: Introductionmentioning
confidence: 99%